MiR-150-5p retards the progression of myocardial fibrosis by targeting EGR1. Issue 12 (18th June 2019) - Shen, Jie; Xing, Wanhong; Gong, Fangqi; Wang, Wei; Yan, Yufeng; Zhang, Yiying; Xie, Chunhong; Fu, Songling
ABSTRACT: To investigate the differential expression of microRNA-150-5p (miR-150-5p) and early growth response 1 ( EGR1) in myocardial fibrosis (MF) cells, and determine the effect between miR-150-5p and EGR1 on MF. Human MF cells were generated via Trypanosoma cruzi ( T. cruzi) infection, a mouse model of MF was generated via angiotensin II. The expression levels of miR-150-5p and EGR1 were detected by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot assay. The correlation between miR-150-5p and EGR1 was confirmed by a luciferase reporter assay. The viability, proliferation, and apoptotic rate were detected by cell counting kit-8 (CCK-8), colony-formation and flow cytometry assays. Hematoxylin-eosin (HE) staining and Masson staining visualized the degree of MF. Echocardiography was performed to obtain the levels of left ventricle fractional shortening (LVFS) and left ventricle ejection fraction (LVEF), computer algorithms and a videographics program were used to obtain the levels of left ventricular systolic pressure (LVSP), left ventricular end diastolic pressure (LVEDP) and ±left ventricular dp/dt maximum (LV dp/dtmax). We found that the expression of miR-150-5p in MF cells was lower than normal cardiomyocytes, while the expression level of EGR1 in MF cells were higher than normal cardiomyocytes. Cell experiments demonstrated that EGR1 and miR-150-5p could influence the development of MF, and the expression of EGR1 in cardiomyocytes was regulated by miR-150-5p directly. Lastly, we confirmed that sh- Egr1 would decrease the severity of MF, while miR-150-5p antagomir could aggravate MF. Our results illustrate the mechanism of MF development, and provide a potential target for MF treatment.